Functional Outcome of Proximal Fibular Osteotomy in Medial Compartment Osteoarthritis of The Knee Joint - Das, Chandan Kumar; Rahman Chowdhury, Md Mizanur; Ghosh, Saikat; Matin, Mohammad Qausarul; Choudhuri, Md Nazrul Islam; Islam, Md Somirul (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Proximal Fibular Osteotomy (PFO) has been proposed as a new surgical option for pain relief in patients with medial compartment knee osteoarthritis. It is simple, safe and affordable. To assess functional outcome of proximal fibular osteotomy in medial compartment osteoarthritis of knee joint. Materials and methods: This prospective hospital based clinical trial was carried out in the Department of Orthopedic Surgery Chittagong Medical College Hospital (CMCH) Chattogram from July 2019 to June 2020. A total of 30 patients with knee osteoarthritis were enrolled through inclusion and exclusion criteria by purposive sampling. Proximal fibular osteotomy was done after taking written informed consent. Data was recorded in a predesigned case record form. All the patients were followed up to 6 months when final outcome was assessed by Oxford Knee Score. All the data were analyzed statistically by using Statistical Package for Social Sciences (SPSS-25). The result was expressed as frequency, percentage and mean ± SD. Level of significance was calculated at p<0.05. Results: In this study, out of 30 cases, majority of the cases (57.7%) was in 55-64 years of age group. Mean ± SD pre-operative and post-operative VAS score were 7.13 ± 1.408 and 2.10 ± 0.803 respectively. According to Oxford Knee Score (OKS) pre-operative and postoperative mean ± SD were, 18.00 ± 2.117 and 36.53 ± 2.403. Mean ± SD pre-operative and post-operative Tibio Femoral Angle were 182.97 ± 1.810 and 178.63 ± 1.377 respectively. Mean ± SD pre-operative and post-operative Medial Joint Space (mm) were 1.223 ± 0.378 and 3.816 ± 0.982 respectively. Mean ± SD pre-operative and postoperative Lateral Joint Space (mm) were 6.640 ± 1.209 and 5.050 ± 0.897 respectively. Conclusion: After analyzing the results of present study, it can be concluded that proximal fibular osteotomy is a new, simple procedure in the management of medial compartment osteoarthritis of the knee which may delay the need for definitive knee procedures like unicompartmental knee arthroplasty or total knee replacement. JCMCTA 2021 ; 32 (2) : 137-141